Предмет: Математика,
автор: alina303123
(4(x + 1) < 3(x - 3) - 2,
{
4(2x - 1)<3(3x - 2).
Приложения:
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
1) 4(х + 1) < 3(x - 3) -x
4x + 4 < 3x - 9 - x
4x - 3x + x < -9 - 4
2x < - 13
x < - 6,5
2) 4 (2x -1) ≤ 3 ( 3x - 2) =
8x - 4 ≤ 9x -6
6 - 4 ≤ 9x - 8x
2 ≤ x
x ≥ 2
3) x < - 6,5 и х ≥ 2 не пересекаются
Похожие вопросы
Предмет: Литература,
автор: bndarenklju
Предмет: Алгебра,
автор: zteredbulv5
Предмет: Английский язык,
автор: Londonparty
Предмет: Химия,
автор: Аллан123